2023
DOI: 10.1051/mfreview/2023001
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure, physical, tensile and wear behaviour of B4C particles reinforced Al7010 alloy composites

Abstract: In the present study looked into how incorporating B4C particles with a size range of 20–25 microns would affect the mechanical, wear and physical properties of composites made from Al7010 alloy. The stir cast method accounted for of the total production of B4C composites. Different mechanical properties, such as hardness, tensile behaviour, wear and density, were measured and analysed for these synthetic composites. Microstructure was characterised by scanning electron microscopy and X-ray diffraction analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…It was also revealed by Kara et al that the tensile strength was increased initially with the addition of B 4 C but further addition of reinforcement resulted in the decrement of tensile strength. Mydur et al [26] studied the microstructural and wear behaviour of Al7010 alloy composites reinforced with B 4 C particulates. The wear tests conducted by the authors showed that the Al7010 alloy with 8 wt% of B 4 C shows more wear resistance as compared to the metal alloy whereas the density was found to be slightly less in the fabricated composites.…”
Section: Introductionmentioning
confidence: 99%
“…It was also revealed by Kara et al that the tensile strength was increased initially with the addition of B 4 C but further addition of reinforcement resulted in the decrement of tensile strength. Mydur et al [26] studied the microstructural and wear behaviour of Al7010 alloy composites reinforced with B 4 C particulates. The wear tests conducted by the authors showed that the Al7010 alloy with 8 wt% of B 4 C shows more wear resistance as compared to the metal alloy whereas the density was found to be slightly less in the fabricated composites.…”
Section: Introductionmentioning
confidence: 99%
“…Composites are materials that combine two or more different constituents to achieve a greater strength than the separate constituents [1][2][3]. They are essential to Brazilian Journal of Development, Curitiba, v.10, n.5, p. 01-23, 2024 many industrial applications.…”
Section: Introductionmentioning
confidence: 99%
“…With the ability to modify their characteristics by adding specific reinforcement, Metal Matrix Composites (MMCs) are gaining popularity as a material for high-tech aerospace applications [1,2]. Due of its exceptional strength and specific stiffness at both room temperature and extreme temperatures, particle reinforced MMCs have lately garnered a lot of attention [3,4]. It is widely recognized that the form, size, orientation, distribution, and volume or weight of the reinforcement are micro-structural characteristics that significantly impact the elastic properties of the metal matrix composite [5].…”
Section: Introductionmentioning
confidence: 99%